Atrial Fibrillation for Stroke Detection - Foong, O.-M. (Springer, 2019)
This paper presents Atrial Fibrillation Detection for Stroke Prevention. Stroke is the third leading cause of death in Malaysia after cancer. Furthermore, one of the risk factors for stroke is Atrial Fibrillation. The objective of this paper is to develop an IoT device that helps to perform early detection of irregular heart beat at affordable cost. However, the devices or gadgets are expensive and a doctor will not be always available to monitor patientâs pulse regularly. Therefore, a real-time heart rate and rhythm monitoring device are presented in this paper. Experimental results show that the proposed device has achieved satisfactory performance in terms of user acceptance testing. Â© 2019, Springer Nature Switzerland AG.